The inaugural speech of the Indonesian presidents: Analysing speech acts of Jokowi and SBY inaugural speech - Hidayat, Didin Nuruddin; Septiawan, Yudi; Eviyuliwati, Ismalianing; Zulfikar, Teuku; Permana, Sudarya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Language plays a significant part in shaping and influencing people’s perspectives on societies and on political sectors, especially in an inaugural speech. Inaugural speech is one of the powerful tools to notify the people of the purposes as a leader. Hence, the researchers aimed to analyze the inaugural speeches of Susilo Bambang Yudhoyono (SBY) in 2004 and Joko Widodo (Jokowi) in 2019 regarding their rhetoric and schematic words in their speeches during their tenure served as the Indonesian President. To uncover their inaugural speeches, the researchers used the theoretical frameworks proposed by Hymes (1974, cited in Eaton, 2019), where he developed the analysis of the connection between a language and a broader feature, such as macro- and micro-linguistics analysis. However, the key purpose of concern still marks a language presenting equality between linguistic and social perspectives. The study revealed that SBY and Jokowi mostly used polite words, a low, moderate voice, and tended to appreciate their rivals when giving their inaugural speeches respectively in 2004 and 2019. The difference in macro and micro-linguistics features assert that these two national figures have different traits even though they are from the same ethnic group, the Javanese. Further, this study suggested some pedagogical implications for English teachers to implement the potential benefits of macro- and micro-linguistics analysis of inaugural speeches for the language classroom. It can bridge a gap between language teaching and practical English use in society.